What kids should know about Andres and the Katipunan - Cahiles, Weng D.; Natividad, isa N. (Quezon City Adarna House, 2015)
"This book is a handy reference for children on the life of the Supremo and the Katipunan."
"This book is recommended for children ages 10 and above."
National Childrens Book Awards: 2014 Best Reads for children winner
Keywords: Philippines -- History -- Revolution, 1896-1898.